Persisting Reductions in Cannabis, Opioid, and Stimulant Misuse After Naturalistic Psychedelic Use: An Online Survey - Garcia-Romeu, Albert; Davis, Alan K.; Erowid, Earth; Erowid, Fire; Griffiths, Roland R.; Johnson, Matthew W. (Frontiers in Psychiatry, 2020)
Background Observational data and preliminary studies suggest serotonin 2A agonist psychedelics may hold potential in treating a variety of substance use disorders (SUDs), including opioid use disorder (OUD). Aims The study aim was to describe and analyze self-reported cases in which naturalistic psychedelic use was followed by cessation or reduction in other substance use. Methods An anonymous online survey of individuals reporting cessation or reduction in cannabis, opioid, or stimulant use following psychedelic use in non-clinical settings. Results Four hundred forty-four respondents, mostly in the USA (67%) completed the survey. Participants reported 4.5 years of problematic substance use on average before the psychedelic experience to which they attributed a reduction in drug consumption, with 79% meeting retrospective criteria for severe SUD. Most reported taking a moderate or high dose of LSD (43%) or psilocybin-containing mushrooms (29%), followed by significant reduction in drug consumption. Before the psychedelic experience 96% met SUD criteria, whereas only 27% met SUD criteria afterward. Participants rated their psychedelic experience as highly meaningful and insightful, with 28% endorsing psychedelic-associated changes in life priorities or values as facilitating reduced substance misuse. Greater psychedelic dose, insight, mystical-type effects, and personal meaning of experiences were associated with greater reduction in drug consumption. Conclusions While these cross-sectional and self-report methods cannot determine whether psychedelics caused changes in drug use, results suggest the potential that psychedelics cause reductions in problematic substance use, and support additional clinical research on psychedelic-assisted treatment for SUD.